“SYAIR JAWI”: MANUSKRIP AMBON - Devi Fauziyah Ma’rifat (Balai Bahasa Provinsi Riau, 2014)
The old manuscript is a record of the past culture, that contains a wide variety of way of life, way of thinking, moral teachings, advice, entertainment, challenge etc. Script is something that is unique, none of the old manuscripts are identical to other texts. While telling about the same thing, but each has different script. Each manuscript is a witness of a civilized world, a tradition of civilization. Philologist tried hard to bridge the time that has past, ignorance of the age of the text was written, to the proper interpretation. Disclosure of text of “Syair Jawi” is done through transliteration, edits, and text analysis. Accordingly, the reader is expected to thoroughly understand, and take the wisdom contained in the text. “Syair Jawi” is written in Ambon malay language, contains advice to readers that all humans will return to God. This study uses a critical issue method. Manuscript “Syair Jawi”, using simple language that is easily understood by readers although grammatically considered to be less fulfilling language. This poem is more concerned with the content of a message, instructions, and knowledge of Islam, the content of “Syair Jawi” include message in order to do good to parents, following the teachings of the prophet Muhammad, beg for forgiveness, remembering the hereafter, the story of the birth of the prophet Muhammad, the benefits of prayers and special prayer for prophet Muhammad. The content of “Syair Jawi” shows that the life of Ambon Malay is very religious, based on the teachings of Islam. This suggests that the culture of Ambon Malay people in the past, was influenced by the Islamic teaching. Naskah kuno adalah catatan dari budaya masa lalu, yang berisi berbagai macam cara hidup, cara berpikir, ajaran moral, saran, hiburan, tantangan, dan lain-lain. Naskah adalah sesuatu yang unik, tidak ada naskah kuno yang identik dengan teks lainnya. Walaupun naskah kuno bercerita tentang hal yang sama, tetapi masing-masing memiliki naskah yang berbeda. Setiap naskah adalah saksi dari dunia yang beradab, tradisi peradaban. Filolog berusaha keras untuk menjembatani waktu yang telah lalu, ketidaktahuan usia teks ditulis, dengan penafsiran yang tepat. Pengungkapan teks ―Syair Jawi‖ dilakukan melalui transliterasi, suntingan, dan analisis teks. Dengan demikian, pembaca diharapkan benarbenar memahami, dan mengambil hikmah yang terkandung dalam teks. ―Syair Jawi‖ ditulis dalam bahasa Melayu Ambon, berisi nasihat kepada pembaca bahwa semua manusia akan kembali kepada Allah. Penelitian ini menggunakan metode isu kritis. Naskah ―Syair Jawi‖, menggunakan bahasa yang sederhana yang mudah dipahami oleh pembaca meskipun secara gramatikal dianggap kurang memuaskan bahasa. Puisi ini lebih peduli dengan isi pesan, petunjuk, dan pengetahuan tentang Islam, isi ―Syair Jawi‖ termasuk pesan untuk berbuat baik kepada orang tua, mengikuti ajaran Nabi Muhammad, mohon maaf, mengingat akhirat, kisah kelahiran nabi Muhammad, manfaat doa, dan doa khusus untuk nabi Muhammad. Isu ―Syair Jawi‖ menunjukkan bahwa kehidupan Ambon Melayu sangat religius, berdasarkan ajaran Islam. Hal ini menunjukkan bahwa budaya Melayu Ambon di masa lalu, dipengaruhi oleh ajaran Islam.